2007
DOI: 10.1071/ah070098
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of a team model of nursing practice using work sampling

Abstract: The increasing number of inexperienced graduates, as well as other levels of nurse such as the enrolled nurse and assistant-in-nursing, requires health service and nursing managers in the acute care sector to rethink the long-preferred "patient allocation" model of care provision. As well, the escalating shortage of registered nurses and subsequent low morale among those remaining in the workforce require hospitals to re-examine skills mix and staffing ratios. This paper presents the results of two work-sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 13 publications
0
25
0
13
Order By: Relevance
“…The work reported here lends support to accepting a hypothesis that teaming in acute nursing yields job satisfaction and staff retention benefi ts. Since the project's conduct, positive results associated with shifting to team-based nursing have been reported from post 2005 nursing literature in Australia (Hayman, Wilkes, & Cioffi , 2008;O'Connell, Duke, Bennett, Crawford, & Korfi atis, 2006;Walker, Donoghue, & Mitten-Lewis, 2007) and North America (Dobson, Adamson, & Drexler, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…The work reported here lends support to accepting a hypothesis that teaming in acute nursing yields job satisfaction and staff retention benefi ts. Since the project's conduct, positive results associated with shifting to team-based nursing have been reported from post 2005 nursing literature in Australia (Hayman, Wilkes, & Cioffi , 2008;O'Connell, Duke, Bennett, Crawford, & Korfi atis, 2006;Walker, Donoghue, & Mitten-Lewis, 2007) and North America (Dobson, Adamson, & Drexler, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…Although the small matched pair sample size is problematic, this study does represent a unique quasi‐experimental study comparing two models of care on job satisfaction. A search of national and international literature on model of care studies between 1996 and 2009 demonstrated that relevant published work employed a non‐experimental descriptive method, 17,34–42 or a single group pre‐test and post‐test design 43–46 . There was only one Canadian study that used a quasi‐experimental design with unrelated samples 47 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the values presented by studies conducted in other contexts, such as surgical centers, nursing homes, and community centers in the U.S. showed higher percentages (15)(16)(17) . We also emphasize the importance of the indirect care provided to users, families and communities, reinforcing the idea that much of what is done by the nursing staff is invisible (18) . Sharing information on care provided was among the most frequent indirect care interventions, which we believe indicates a positive and important result, as it strengthens communication, work relationships between team professionals, and collaborative practices.…”
Section: Discussionmentioning
confidence: 99%